Сonditions of Formation of Cognitive Meta-Subject Results in Younger Schoolchildren - Zak A.Z (Moscow State University of Psychology and Education, 2018)
The article presents a study aimed at evaluating the author's program "Intellectics" as a condition for the formation of cognitive actions in younger schoolchildren. This program includes search tasks for non-curricular content of a different kind and types, which were solved by fourth-graders in group form during off-hour time in 32 classes during the school year. The author's technique "Substitution" is presented, which includes two tasks: to determine the formation of a method for solving search problems (general or particular) and the formation of reflection in solving problems (meaningful or formal). For the first time, , the results indicating the significant impact of the program "Intellektika" on the achievement of children of high metasubject educational results.